CD39 improves survival in microbial sepsis by attenuating systemic inflammation. Issue 1 (15th October 2014) - Csóka, Balázs; Németh, Zoltán H.; Törő, Gábor; Koscsó, Balázs; Kókai, Endre; Robson, Simon C.; Enjyoji, Keiichi; Rolandelli, Rolando H.; Erdélyi, Katalin; Pacher, Pal; Haskó, György
Abstract : Sepsis remains the leading cause of morbidity and mortality in critically ill patients. Excessive inflammation is a major cause of organ failure and mortality in sepsis. Ectonucleoside triphosphate diphosphohydrolase 1, ENTPDase1 (CD39) is a cell surface nucleotide‐metabolizing enzyme, which degrades the extracellular purines ATP and ADP, thereby regulating purinergic receptor signaling. Although the role of purinergic receptor signaling in regulating inflammation and sepsis has been addressed previously, the role of CD39 in regulating the host's response to sepsis is unknown. We found that the CD39 mimic apyrase (250 U/kg) decreased and knockout or pharmacologic blockade with sodium polyoxotungstate (5 mg/kg; IC50 ã 10 μM) of CD39 increased mortality of mice with polymicrobial sepsis induced by cecal ligation and puncture. CD39 decreased inflammation, organ damage, immune cell apoptosis, and bacterial load. Use of bone marrow chimeric mice revealed that CD39 expression on myeloid cells decreases inflammation in septic mice. CD39 expression is upregulated during sepsis in mice, as well as in both murine and human macrophages stimulated with Escherichia coli . Moreover, E. coli increases CD39 promoter activity in macrophages. Altogether, these data indicate CD39 as an evolutionarily conserved inducible protective pathway during sepsis. We propose CD39 as a novel therapeutic target in the management of sepsis—Csóka, B., Németh, Z. H., Törő, G., Koscsó, B., Kókai, E., Robson, S. C., Enjyoji, K., Rolandelli, R. H., Erdélyi, K., Pacher, P., Haskó, G., CD39 improves survival in microbial sepsis by attenuating systemic inflammation. FASEB J. 29, 25–36 (2015). www.fasebj.org